Efektivitas Penggunaan E-court Terhadap Efisiensi Proses Peradilan di Pengadilan Agama Maros Kelas 1B - Haleda, Alya Nabila; Baedah, Said Syarifuddin Abu; Akil, M. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effectiveness of the e-Court system in improving the efficiency of the judicial process at the Maros Class 1B Religious Court. In this case, the field research is qualitative, using a qualitative approach with the aim of explaining what actually happens in the field descriptively with an analysis method in order to be able to understand more thoroughly the research location to obtain appropriate data, by obtaining oral and written data at the research location located at the Maros Class 1B Religious Court.The results of the study indicate that the use of e-court in fulfilling the efficiency of the case resolution process at the Maros Class 1B Religious Court cannot be said to be fully efficient, there are several stages that still have obstacles, at the registration stage (e-filling) it is completely said to be efficient for court employees and the parties to the case, the second stage of the payment stage (e-payment) is easy but the obstacles at the Maros Class 1B Religious Court at this stage there are other obstacles such as parties who do not pay attention to the payment deadline, which results in them being late in getting the case number. Furthermore, at the Summons stage (e-summons) the obstacle faced by the court is that PT. POS does not understand the summons rules. As well as the trial stage (e-litigation) there are obstacles found for the parties, namely uploading the wrong documents.